RUANG LIPSCHITZ - Agustian, Muhammad Rifqi; Rosjanuardi, Rizky; Mulyaning Asih, Endang Cahya (Program Studi Matematika Jurusan Pendidikan Matematika FPMIPA UPI, 2017)
ABSTRAK. Diberikan ruang metrik dan lapangan (real atau kompleks). Suatu fungsi dikatakan fungsi Lipschitz bernilai skalar jika terdapat konstanta sedemikian sehingga Ruang Lipschitz adalah ruang dari semua fungsi Lipschitz terbatas bernilai skalar pada . Didefinisikan penjumlahan dan perkalian skalar pada dengan aturan dan , .Ruang Lipschitz dilengkapi dengan norm Lipschitz yang didefinisikan sebagai.Kajian ini mengkaji sifat-sifat dari fungsi Lipschitz bernilai skalar dan hubungannya dengan ruang Banach. Kata kunci: fungsi Lipschitz, fungsi Lipschitz bernilai skalar, ruang Lipschitz, ruang Banach, norm Lipschitz. ABSTRACT. Given a metric space and a field (real or complex). A function is said to be scalar-valued Lipschitz function if there exists a constant such that Lipschitz space is the space of all bounded scalar valued Lipschitz function on . Addition and scalar multiplication defined on with and , .Lipschitz space equipped with norm Lipschitz which is defined by.This study observes the properties of scalar valued Lipschitz function and its relationship with Banach Space. Keywords: Lipschitz function, scalar valued Lipschitz function, Lipschitz space, Banach space, Lipschitz norm.